Implementasi Pembelajaran Akuntansi Sesuai Kurikulum 2013 Pada Guru-Guru SMK Program Keahlian Akuntansi Di Kota Klaten - Fatmawati, Chandra Diksi, Dr.Suyatmini,SE.,M.Si (2017)
The purpose of this research are 1) the lesson planning, implementation and assesment of accounting learning based on curriculum 2013 2) the factors that inhibitting on the implementation of accounting learning based on curicullum 2013 3) solution for that the factors. This is a qualitative research. The object of this research are teachers of vocational school Klaten. Data collection techniques are using interviews, observation and documentation. The result for this research are show the teachers of vocational school already planning an appropriate learning material based on curriculum 2013. However, in the practice not all the teachers are able to form an appropriate learning material based on curriculum 2013. Similarly, in the assesment of accounting learning process, not all teachers did the authentic assesment. So that the implementation of accounting learning based on curriculum 2013 in vocational school of Klaten still found the inhibiting factors in the formation of accounting learning. Keyword: implementation of curriculum 2013, accounting learning, planned, implementation, assesment, saintific, authentic.